LITHIUM RAW POTENTIAL IN RUSSIA - Grigory Yu. Boyarko; Vitaly Yu. Khatkov; Evganiya V. Tkacheva (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2022)
The relevance of the work is caused by the problems of Russia's total import dependence on lithium raw materials in the absence of national production of this critical raw material. Purpose: to study lithium raw material base in Russia and the prospects of national production of its extraction. Methods: content analysis of all information on the subject of the mineral resource base of lithium in Russia. Results. Currently, the state of the Russian lithium production industry is characterized by the absence of national extraction of lithium raw materials and total import dependence on lithium carbonate. The steadily growing demand for lithium from battery manufacturers, which has caused an unprecedented increase in world prices for lithium products, creates favorable prerequisites for the activation of the domestic lithium industry. The reconstruction of the national production of strategic lithium raw materials for its import substitution is possible, first of all, by the commissioning of hydromineral deposits of underground brines in the infrastructures of existing oil and gas producing enterprises and other economic entities. The most promising pilot project is associated with lithium production at the Kovykta gas field in Eastern Siberia. The well-known prepared deposits of the traditional technological type of spodumene pegmatite’s in Russia for a long time were unattractive in terms of morally and technically outdated technical and economic indicators, and only in the conditions of a sharp increase in prices for lithium products in 2021–2022, investors' interest in them resumed. In the conditions of high prices for lithium raw materials, projects for development of spodumene pegmatite deposits, primarily the Kolmozersky deposit in the Murmansk region, are also becoming attractive. It is necessary to reassess the well-known Russian spodumene pegmatite deposits near the developed industrial infrastructures, taking into account modern economic conditions and new technologies for processing lithium raw materials. New exploration work may lead to the discovery of new deposits of spodumene pegmatite, which is realized by the example of the search for Tasheglinskaya Square in the Kemerovo region.